A Comprehensive Process Guide to ERP Implementation and Its Challenges - Ulisi, Uma Maheswara Rao (International Journal of Computer Sciences and Engineering, 2025)
Cloud Enterprise Resource Planning (ERP) systems are crucial in streamlining business processes, integrating various functions, and improving organizational efficiency. This paper presents a comprehensive process guide for ERP implementation, detailing each phase from planning and selection to deployment and post-implementation support. Additionally, it addresses the common challenges organizations face during ERP implementation, including data migration, user adoption, system customization, and change management issues. By exploring these challenges and providing actionable insights, this paper aims to guide businesses with the knowledge to navigate the complexities of ERP implementation successfully. Through a combination of practical steps and real-world examples, this guide is a valuable resource for organizations seeking to optimize their ERP systems and ensure long-term success.